What Motivates Internet Financial Reporting in the Public Sector? Case of a Local Government in Indonesia - Juniantika, Dhita Aira; Hapsari, Dini Wahjoe (Journal of Accounting Research, Organization and Economics, 2020)
Objective This study aims to examine the influence of local government wealth, local government debt levels, and audit opinions on Internet Financial Reporting (IFR) in districts / cities in West Java Province, Indonesia, during the period of 2014-2018. Design/methodology This study uses panel data regression analysis. Purposive sampling method is utilized with a total of 65 samples consisting of 13 official sites of district/city governments in West Java Province, Indonesia. The period of this research in total is five years. Results The results of this study indicate that wealth of local governments, local government debt levels, and audit opinions simultaneously influence IFR at 9.81%. Partially the variable of local government wealth and the debt level of local government do not affect IFR, while the audit opinion variable influences IFR in districts/cities in West Java Province during 2014-2018.